A missing member of conjugated N-heterocycles: realizing pyrido[1, 2-α]azepine by reacting ruthenium alkenylcarbene complex with alkyne. Issue 32 (4th April 2018) - Zhou, Xiaoxi; Huang, Fanping; Tang, Chun; Zhuo, Qingde; Chen, Zhixin; Zhang, Hong; Xia, Haiping
Abstract : The first successful chemical synthesis and characterization of a bicyclic pyrido[1, 2-α]azepine ring system. Abstract : Despite the excellent chemical properties of N-heterocycles, pyrido[1, 2-α]azepine remains elusive due to its potential antiaromaticity and lability. Herein, we demonstrate the synthesis and characterization of the first bicyclic pyrido[1, 2-α]azepine that leverages the coordination to the ruthenium center to promote the stability of N-bridged bicycle.